2008
DOI: 10.1002/art.23545
|View full text |Cite
|
Sign up to set email alerts
|

Duffy antigen receptor for chemokines and CXCL5 are essential for the recruitment of neutrophils in a multicellular model of rheumatoid arthritis synovium

Abstract: Objective. The role of chemokines and their transporters in rheumatoid arthritis (RA) is poorly described. Evidence suggests that CXCL5 plays an important role, because it is abundant in RA tissue, and its neutralization moderates joint damage in animal models of arthritis. Expression of the chemokine transporter Duffy antigen receptor for chemokines (DARC) is also up-regulated in early RA. The aim of this study was to investigate the role of CXCL5 and DARC in regulating neutrophil recruitment, using an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…The in vitro study by Smith et al [16] provides convincing evidence that DARC is important in neutrophil migration using an RA model. However, the only study investigate DARC expression in human RA found high levels on the synovial endothelium, but similar levels in patients with osteoarthritis.…”
Section: Darc and Autoimmune Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…The in vitro study by Smith et al [16] provides convincing evidence that DARC is important in neutrophil migration using an RA model. However, the only study investigate DARC expression in human RA found high levels on the synovial endothelium, but similar levels in patients with osteoarthritis.…”
Section: Darc and Autoimmune Diseasesmentioning
confidence: 91%
“…DARC acts on CXCR5 to increase neutrophil migration to affected synovium. Furthermore, blocking the DARC interaction prevents neutrophil recruitment [16].…”
Section: Darc and Autoimmune Diseasesmentioning
confidence: 99%
“…CXCL5 (known as LPS-induced CXC chemokine [LIX] in mice and epithelial cell-derived neutrophil-activating peptide-78 in human) is a unique member of ELR + CXC family of chemokines, which are responsible for mediating neutrophil recruitment into tissues during inflammation and infection (17). ENA-78 has been found to be involved in a variety of human inflammatory diseases (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), such as chronic obstructive pulmonary disease, exacerbation of asthma and chronic obstructive pulmonary disease, acute coronary syndromes, diabetes mellitus, and inflammatory bowel diseases. Murine Cxcl5 was first cloned as a LPS response gene that could be attenuated by glucocorticoids (28).…”
mentioning
confidence: 99%
“…It supports transcytosis of chemokines from luminal to extravascular space and favours leucocyte migration and development of inflammatory reactions [36]. A similar mechanism might operate in in vitro model of rheumatoid arthritis in which overexpression of DARC does favour inflammatory reaction [37]. DARC could play a role in inflammatory diseases of the kidney [38].…”
Section: Duffy Antigensmentioning
confidence: 90%